The Effect of Special Exercises on Developing the Rolling Speed and Accuracy of Shooting in Futsal - Kadhim, Turki Hilal; Abdulridha, Samer Saadoon; Murad, Nermin Hassan (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The aim of the research is to prepare special exercises to develop the rolling speed skill and shooting accuracy in futsal, and to investigate the effect of these special exercises on developing the rolling speed and shooting accuracy in futsal. The researchers used the experimental method as it is suitable for the nature of the research. The research community and sample were defined as futsal players in Diyala Governorate, and the sample was randomly selected through a lottery from the Shahrban Futsal Club, consisting of 16 players. The two programs were distributed by lottery, representing 100% of the research community. The researchers concluded that the special exercises have a positive effect on certain physical abilities and qualities, in addition to their positive effect on the rolling speed and shooting accuracy in futsal. They also found that the variety of skill exercises had a positive effect on some physical abilities and shooting skills in futsal. The high-intensity interval training method contributed directly and positively to developing some physical abilities and the rolling and shooting skills in futsal. The researchers reached several recommendations, including relying on special exercises in training curricula, especially for younger age groups (minors, juniors, and youth), conducting similar studies for other age groups with different training methods concerned with developing physical abilities and basic skills, and understanding the results of these studies.